PERTANGGUNGJAWABAN PIDANA TERHADAP DOKTER YANG MELAKUKAN TINDAKAN MALPRAKTEK DIKAJI DARI KITAB UNDANG-UNDANG HUKUM PIDANA INDONESIA - Indra Diputra, I Gede; Ari Yuliartini Griadhi, Ni Made (Kertha Negara : Journal Ilmu Hukum, 2014)
The paper is titled "Criminal Liability Actions Against Physicians Who PerformMalpractice Assessed From the Criminal Justice Act" This paper uses analytical methods andapproaches normative legislation. Doctor is obliged to provide the best possible medical care forpatients, medical care may be provide medical treatment according to standard medical carenecessary to cure patients, but doctors sometimes results achieved are not as expected due to lackof skills and knowledge that lead to malpractice physician (medical mistakes done by thephysician) to the patient that causes disability or death, so not make lost of justice in the new Actneed a new justice in Criminal Justice for in a special thread for a criminal liability doctor actMalpractice in order to have a justice for victims.
Keywords: Malpractice, Doctor, Criminal Liability, The Book Of The Criminal Law